Polyoxygenated dihydropyrano[ 2,3-c]pyrrole-4,5-dione derivatives from the marine mangrove-derived endophytic fungus Penicillium brocae MA-231 and their antimicrobial activity - Meng, Ling-Hong; Li, Xiao-Ming; Liu, Yang; Wang, Bin-Gui (Chinese chemical letters, 2015)
A new polyoxygenated dihydropyrano[2,3-c]pyrrole-4,5-dione derivative, pyranonigrin F （1）, together with a related known compound, pyranonigrin A （2）, were isolated and identified from Penicillium brocae MA-231, an endophytic fungus obtained from the fresh tissue of the marine mangrove plant Avicennia marina. The structures of these metabolites were determined based on comprehensive spectral interpretation and the absolute configuration of compound 1 was established by X-ray crystallographic analysis. Compounds 1 and 2 showed potent activity against a broad spectrum of human-, aqua-, and plant-pathogens.